Contribution of different organs to grain filling in durum wheat under Mediterranean conditions. 1: Contribution of post-anthesis photosynthesis and remobilization - Merah, O.; Monneveux, P. (Wiley, 2015)
Under Mediterranean conditions, drought affects cereals production principally through a limitation of grain filling. In this study, the respective role of post‐anthesis photosynthesis and carbon remobilization and the contribution of flag leaf, stem, chaff and awns to grain filling were evaluated under Mediterranean conditions in durum wheat (Triticum turgidum var. durum) cultivars. For the purpose, we examined the effects of shading and excision of different parts of the plant and compared carbon isotope discrimination (Δ) in dry matter of flag leaf, stem, chaff, awns and grain at maturity and in sap of stem, flag leaf, chaff and awns, this last measurement providing information on photosynthesis during a short period preceding sampling. Source–sink manipulations and isotopic imprints of different organs on final isotope composition of the grain confirmed the high contribution of both carbons assimilated by ears and remobilized from stems to grain filling, and the relatively low contribution of leaves to grain filling. Grain Δ was highly and significantly associated with grain yield across treatments, suggesting the utilization of this trait as an indicator of source–sink manipulations effects on grain yield. Chaff and awns Δ were better correlated with grain Δ than stem and leaf Δ, indicating that chaff were more involved in grain filling than other organs. Moreover, in chaff, sap Δ was highly significantly correlated with dry matter Δ. These results suggest the use of Δ for a rapid and non‐destructive estimation of the variation in the contribution of different organs to grain filling.